ONOMATOPEYALARNING TARJIMASI: BADIIY MATNLAR MISOLIDA ILMIY TAHLIL (KONFERENSIYA, 2025)
In this article the linguistic characteristics and translation  challenges of rendering English onomotopoeias  into Uzbek ,focusing on their stylistic and functional roles within literary texts .The research is based on a table containing various onomatopoeic units natural sounds .  Onomatopoeias ,  which  strenghten  imagery ,emotional tone ,and expressiveness in literary language ,require careful strategies to achieve  proper equivalence in translation .The article  compares translation approaches  to sound –imitating words related  to animals such as –cats ,dogs and birds as well as other sound sources . Aditionally , examples from literary works are used to highlight the importance of maintaining  semantic , phonetic and stylistic  consistency in translation